Narażenie zawodowe i środowiskowe na azbest w świetle obowiązujących aktów prawnych = Environmental and occupational exposure to asbestos in the light of applicable legislation - Anna Kowalczyk; Ewelina Kozłowska; Jolanta Pacian (Kazimierz Wielki University, 2015)
Kowalczyk Anna, Kozłowska Ewelina, Pacian Jolanta. Narażenie zawodowe i środowiskowe na azbest w świetle obowiązujących aktów prawnych = Environmental and occupational exposure to asbestos in the light of applicable legislation. Journal of Education, Health and Sport. 2015;5(9):481-492. ISSN 2391-8306. DOI10.5281/zenodo.31188 http://dx.doi.org/10.5281/zenodo.31188 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A481-492 https://pbn.nauka.gov.pl/works/628587 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 15.09.2015.   Narażenie zawodowe i środowiskowe na azbest w świetle obowiązujących aktów prawnych   Environmental and occupational exposure to asbestos in the light of applicable legislation   Anna Kowalczyk1, Ewelina Kozłowska2, Jolanta Pacian3   1. Studenckie Koło Naukowe Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 2. Samodzielna Pracownia Epidemiologii, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie 3. Katedra Zdrowia Publicznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie   Autor do korespondencji / Author for correspondence lic. Anna Kowalczyk e-mail: annakowalczyklublin@gmail.com   STRESZCZENIE Azbest stwarza ogromne zagrożenie zdrowotne. Jest szczególnie niebezpieczny w procesie wydobywania i produkcji, podczas obróbki, eksploatacji, usuwania,  w wyniku uszkodzeń lub korozji wyrobów zawierających azbest. Celem pracy jest przedstawienie regulacji prawnych dotyczących środowiskowego i zawodowego narażenia na azbest. Przedmiotem analizy są akty prawne dotyczące: zakazu stosowania azbestu, bezpieczeństwa i higieny pracy w narażeniu na azbest, gospodarki i transportu odpadów azbestowych, budownictwa oraz szeroko pojętej ochrony środowiska przed szkodliwym działaniem azbestu. W pracy szczegółowo omówiono zasady ochrony zdrowia pracowników i byłych pracowników narażonych na azbest. Przybliżono podstawowe założenia programu wieloletniego pt. "Program Oczyszczania Kraju z Azbestu na lata 2009-2032". Zastosowaną metodą była metoda dogmatyczna oraz prawno-porównawcza polegająca na analizie aktów prawnych oraz dostępnej literatury.   Słowa kluczowe: azbest, narażenie zawodowe, narażenie środowiskowe, akty prawne.       ABSTRACT Asbestos creates a huge threat. It is particularly dangerous in the process of extraction and production, while processing, use, disposal or as a result of damage or corrosion of products containing asbestos. An aim of the work is to present regulations concerning environmental and occupational exposure to asbestos. The subject of analysis are legislative acts relating: prohibition of asbestos use, health and safety at work in exposure to asbestos, management and transport of asbestos waste, construction and widely comprehended environmental protection before harmful effect of asbestos. The work in detail describes principles of health protection of the employees and former employees exposed to asbestos. Presented basic assumptions of long-term program entitled "Program of Cleaning the Country from Asbestos for 2009-2032 years". Dogmatic and legal-comparative method was the applied method consisting in analysis of legislative acts and available literature.   Keywords: asbestos, occupational exposure, environmental exposure, legislative acts.